2009
DOI: 10.1002/pssr.200802238
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of the shear viscosity of thermally aged bulk and ribbon glassy Pd40Cu30Ni10P20 by rapid quenching from the supercooled liquid state

Abstract: The recovery of the shear viscosity of thermally aged bulk and ribbon glassy Pd 40 Cu 30 Ni 10 P 20 by rapid quenching from the supercooled liquid state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is important to investigate whether the annealing-induced loss of the deformation ability is truly irreversible or it can be recovered by a special heat treatment of glass. It was earlier found that the shear viscosity [3], stress relaxation ability [4,5], low frequency viscoelastic internal friction [6] as well as high-frequency shear modulus [7,8] of aged glassy Pd 40 Cu 30 Ni 10 P 20 can be recovered by rapid quenching from the supercooled liquid state (i.e. from temperatures T > T g ) indicating the recovery of structural relaxation lost in the course of preannealing.…”
Section: Introductionmentioning
confidence: 97%
“…It is important to investigate whether the annealing-induced loss of the deformation ability is truly irreversible or it can be recovered by a special heat treatment of glass. It was earlier found that the shear viscosity [3], stress relaxation ability [4,5], low frequency viscoelastic internal friction [6] as well as high-frequency shear modulus [7,8] of aged glassy Pd 40 Cu 30 Ni 10 P 20 can be recovered by rapid quenching from the supercooled liquid state (i.e. from temperatures T > T g ) indicating the recovery of structural relaxation lost in the course of preannealing.…”
Section: Introductionmentioning
confidence: 97%
“…The first reports on partial or even full disembrittlement produced by annealing below T g were published in the 1980s and beginning of 1990s of the past century . There are several later papers dealing with the recovery of mechanical properties deteriorated by the preceding structural relaxation below T g . The rejuvenation procedure in the majority of instances included heating of aged samples into the supercooled liquid region (i.e., above T g ) and subsequent fast cooling at the rates comparable with the production quenching rate (≈10 2 K s −1 ) or even bigger .…”
mentioning
confidence: 99%
“…There are several later papers dealing with the recovery of mechanical properties deteriorated by the preceding structural relaxation below T g . The rejuvenation procedure in the majority of instances included heating of aged samples into the supercooled liquid region (i.e., above T g ) and subsequent fast cooling at the rates comparable with the production quenching rate (≈10 2 K s −1 ) or even bigger . In the latter case, the rejuvenation can lead to opposite property changes exceeding by the absolute value those occurring upon preceding structural relaxation below T g .…”
mentioning
confidence: 99%